In vivo monitoring of parathyroid hormone treatment after myocardial infarction in mice with [68Ga]annexin A5 and [18F]fluorodeoxyglucose positron emission tomography - Lehner, Sebastian; Todica, Andrei; Vanchev, Yordan; Uebleis, Christopher; Wang, Hao; Herrler, Tanja; Wängler, Carmen; Cumming, Paul; Böning, Guido; Franz, Wolfgang M; Bartenstein, Peter; Hacker, Marcus; et al. (Molecular Imaging, 2014)
[68Ga]Annexin A5 positron emission tomography (PET) reveals the externalization of phosphatidylserine as a surrogate marker for apoptosis. We tested this technique for therapy monitoring in a murine model of myocardial infarction (MI) including parathyroid hormone (PTH) treatment. MI was induced in mice, and they were assigned to the saline or the PTH group. On day 2, they received [68Ga]annexin A5 PET or histofluorescence TUNEL staining. Mice had 2-deoxy-2-[18F]fluoro-d-glucose (FDG)-PET examinations on days 6 and 30 for calculation of the left ventricular ejection fraction and infarct area. [68Ga]Annexin A5 uptake was 7.4 ± 1.3 %ID/g within the infarction for the controls and 4.5 ± 1.9 %ID/g for the PTH group (p = .013). TUNEL staining revealed significantly more apoptotic cells in the infarct area on day 2 in the controls (64 ± 9%) compared to the treatment group (52 ± 4%; p = .045). FDG-PET revealed a significant decrease in infarct size in the treatment group and an increase in the controls. Examinations of left ventricular ejection fraction on days 6 and 30 did not reveal treatment effects. [68Ga]Annexin A5 PET can detect the effects of PTH treatment as a marker of apoptosis 2 days after MI; ex vivo examination confirmed significant rescue of myocardiocytes. FDG-PET showed a small but significant reduction in infarct size but no functional improvement.
EVALuna2:13846